Performance of Klebsiella oxytoca to Generate Electricity from POME in Microbial Fuel Cell - Islam, M. Amirul (EDP Sciences, 2016)
This study is aimed to evaluate the electricity generation from microbial fuel cell (MFC) and to analyze the microbial community structure of city wastewater and anaerobic sludge to enhance the MFC performance. MFCs, enriched with palm oil mill effluent (POME) were employed to harvest electricity by innoculating of Klebsiella oxytoca, collected from city wastewater and other microbes from anaerobic sludge (AS). The MFC showed maximum power density of 207.28 mW/m3 with continuous feeding of POME using microbes from AS. Subsequent replacement with Klebsiella oxytoca resulted maximum power density of 1236 mW/m3 by utilizing complex substrate POME which was six times higher as compared to MFC operated with AS. Based on Biolog gene III analysis, relatively higher abundance of Klebsiella oxytoca was detected in the city wastewater. Predominant microorganisms such as Gammaproteobacteria, Azospiraoryzae, Acetobacterperoxydans and Solimonasvariicoloris were isolated from palm oil anaerobic sludge as well as from biofilm of MFC. Enriched electrochemically active bacteria Klebsiella oxytoca showed better performance to generate electricity from complex POME substrates compare to AS. These results demonstrate that the power output of MFCs can be increased significantly using Klebsiella oxytoca.